2020
DOI: 10.1155/2020/5158497
|View full text |Cite
|
Sign up to set email alerts
|

ADIPOQ rs2241766 Gene Polymorphism and Predisposition to Diabetic Kidney Disease

Abstract: Background. This meta-analysis was performed to obtain a more comprehensive estimation of the role of the single nucleotide polymorphism (SNP) rs2241766 in the ADIPOQ gene in the occurrence of diabetic kidney disease (DKD). Methods. Relevant studies were identified from digital databases such as Embase, PubMed, Medline, Cochrane Library, Google Scholar, WanFang, and Chinese National Knowledge Infrastructure (CNKI). Odds ratios (ORs) with their corresponding 95% confidence intervals (95% CIs) were pooled by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The incidence of diabetes mellitus (DM) has gradually increased with the development of a social economy, and the number of patients with diabetes is expected to exceed 693 million by 2045 [ 1 ]. Approximately 40% of diabetic patients are prone to the development of diabetic nephropathy (DN) [ 2 4 ]. DN is one of the most common microvascular complications of diabetes and is considered the most common cause of end-stage renal disease (ESRD) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of diabetes mellitus (DM) has gradually increased with the development of a social economy, and the number of patients with diabetes is expected to exceed 693 million by 2045 [ 1 ]. Approximately 40% of diabetic patients are prone to the development of diabetic nephropathy (DN) [ 2 4 ]. DN is one of the most common microvascular complications of diabetes and is considered the most common cause of end-stage renal disease (ESRD) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…DKD is a polygenic disease ( 18 ). A long list of genes have been identified to play a contributory role in the pathogenesis of DKD, such as ADIPOQ gene ( 19 ) and IL-6 gene ( 20 ). However, the results are not often reproducible at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…UA has recently been certified as a risk factor for the development, prognosis, and progression of IMN [5,6,7,9,21,22], which also leads to kidney inflammation in a lens-dependent and -independent manner [23]. The research showed that UA may firstly activate the NLRP3 inflammatory pathway.…”
Section: Discussionmentioning
confidence: 99%